2021
DOI: 10.3390/s21020547
|View full text |Cite
|
Sign up to set email alerts
|

Power-over-Fiber LPIT for Voltage and Current Measurements in the Medium Voltage Distribution Networks

Abstract: In this work, we present the design, laboratory tests, and the field trial results of a power-over-fiber (PoF) low power instrument transformer (LPIT) for voltage and current measurements in the medium voltage distribution networks. The new proposed design of this power-over-fiber LPIT aims to overcome the drawbacks presented by the previous technologies, such as the continuous operation (measuring and data transmission) for a wide current range conducted in the medium voltage transmission lines, damage due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Smart buildings, monitoring, and management systems played an important role in the efficient control of the building services like electrical energy consumption [7]- [9], and security [10]. Therefore; the necessity to build a low cost and efficient monitoring system increased to cover the requirements of smart Indonesian J Elec Eng & Comp Sci ISSN: 2502-4752  Control of gas pipeline leakage detection based on hybrid inline fiber interferometer (Nada F. Noori) 749 buildings especially in hospitals [11].…”
Section: Introductionmentioning
confidence: 99%
“…Smart buildings, monitoring, and management systems played an important role in the efficient control of the building services like electrical energy consumption [7]- [9], and security [10]. Therefore; the necessity to build a low cost and efficient monitoring system increased to cover the requirements of smart Indonesian J Elec Eng & Comp Sci ISSN: 2502-4752  Control of gas pipeline leakage detection based on hybrid inline fiber interferometer (Nada F. Noori) 749 buildings especially in hospitals [11].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced technologies such as digital technologies, communication systems, and standards have all laid the way for the upgrade of power systems to smart grids, which is playing a role in the development of fault detection, measurement, and control applications to meet the demands of the modern era [1]. Reliability and safety are increasingly dependent on the accuracy and speed of directly measuring electrical quantities (current, voltage, frequency, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Authors in [ 19 ] demonstrated a PoF-based system designed to power IoT sensors (temperature and humidity), attaining 279 mW of delivered electrical power with efficiency of 16.5%. Bassan et al [ 20 ] employed PoF for voltage and current measurements in medium voltage distribution networks, reaching 80 mW of electrical power, which was used to power a low threshold laser, electronic circuits, and sensors.…”
Section: Introductionmentioning
confidence: 99%